Using ferromagnetic nanoparticles with low Curie temperature for magnetic resonance imaging-guided thermoablation - Herynek, Vit; Turnovcova, Karolina; Veverka, Pavel; Dědourková, Tereza; Žvátora, Pavel; Jendelová, Pavla; Gálisová, Andrea; Kosinová, Lucie; Jiráková, Klara; Syková, Eva (Dove Medical Press Ltd, 2016)
Magnetic nanoparticles represent a tool for use in magnetic resonance imaging (MRI)-guided thermoablation of tumors using an external high-frequency mag¬netic field. To avoid local overheating, perovskite nanoparticles with a lower Curie temperature (Tc) were proposed for use in thermotherapy. However, deposited power decreases when approaching the Curie temperature and consequently may not be sufficient for effective ablation. The goal of the study was to test this hypothesis. Perovskite nanoparticles (Tc = 66–74°C) were characterized and tested both in vitro and in vivo. Magnetic particles with low Tc can be tracked in vivo by MRI and heated by a HF field. The particles are capable of inducing cell apoptosis in suspensions in vitro at high concentrations only.
Využití feromagnetických nanočástic s nízkou Curieovou teplotou pro zobrazovací magnetickou rezonancí řízenou termoablaci
Keywords: perovskite nanoparticles; hyperthermia; high-frequency magnetic field; MRI; tumor ablation; perovskitové nanočástice; hypertermie; vysokofrekvenční magnetické pole; MRI; ablace tumoru